Mobile Secured IoT Sensors-Driven Network Using Efficient QoS Management - Mohammad Siraj; Majid Altamimi; Zeeshan Ahmad Abbasi (IEEE Access)
Autonomous services use future networks with consumer electronic devices for the growth of real-time systems. The Internet of Things (IoT) collects data from unpredictable networks using wireless systems and forwards it toward analyzing servers. Due to the uncertain behavior of devices, next-generation technologies pose significant research challenges while maintaining load balance communication and device mobility. Most solutions enhance the management of data flow using centralized computing, but distributed and heterogeneous channels still cause reliability issues. With the use of mobile agents, this research offers quality-aware services and a cooperative protocol for unbalanced IoT networks. Examining the mobility patterns of devices, it effectively achieves massive amounts of data across established connections and lowers communication faults for diverse services. Furthermore, the routes are optimized by integrating energy and resource constraints. To increase the trustworthiness of dynamic networks, mobile devices interact with intelligence with lightweight processing strategies. Secondly, different performance metrics are incorporated to assess the robustness of security for emerging IoT applications. The significance of the proposed protocol is evaluated and experimental results revealed its noteworthy performance other than state-of-the-art schemes.